2008
DOI: 10.1200/jco.2008.16.5720
|View full text |Cite
|
Sign up to set email alerts
|

Results of the EICESS-92 Study: Two Randomized Trials of Ewing's Sarcoma Treatment—Cyclophosphamide Compared With Ifosfamide in Standard-Risk Patients and Assessment of Benefit of Etoposide Added to Standard Treatment in High-Risk Patients

Abstract: Cyclophosphamide seemed to have a similar effect on EFS and OS as ifosfamide in SR patients but was associated with increased toxicity. In HR patients, the addition of etoposide seemed to be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
160
0
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(177 citation statements)
references
References 24 publications
8
160
0
9
Order By: Relevance
“…Eleven (37%) of these primary tumors were located in the femur, nine (30%) in the pelvis, six (20%) in the tibia, four (13%) in the fibula. (Neo)adjuvant chemotherapy was given according to recommended protocols (Table 1) [10,20,23].…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven (37%) of these primary tumors were located in the femur, nine (30%) in the pelvis, six (20%) in the tibia, four (13%) in the fibula. (Neo)adjuvant chemotherapy was given according to recommended protocols (Table 1) [10,20,23].…”
Section: Patientsmentioning
confidence: 99%
“…Ewing's sarcoma differs from osteosarcoma in some respects: the mean age of the patients is younger than those with osteosarcoma and seldom occurs beyond the age of 30 years, local control can be achieved with radiation as well as resection, and the drugs used to treat Ewing's sarcoma are different than those used to treat osteosarcoma [3,20,31]. In addition to adequate local control, the use of aggressive polychemotherapy has remarkably improved the survival of patients with Ewing's sarcoma [10,25,32,37] since adjuvant chemotherapy was first introduced in the 1980s and has led to a growing number of long-term survivors [8,20,23]. However, chemotherapy can result in long-term late effects on the cardiac, pulmonary, and metabolic systems as well as on skeletal muscle [16].…”
Section: Introductionmentioning
confidence: 99%
“…20,21,23,36 The 7-year EFS of 61%, achieved with the ETC conditioning regimen, seems encouraging, especially considering the survival reported in studies with conventional chemotherapy [18][19][20][21] in which the EFS was always o40%. Nevertheless, Paulussen et al 22 recently reported a 5-year EFS of 55% in high-risk ESFT using an intensive induction chemotherapy (EVAIA regimen) without HDC/ASCT, confirming that the effect of HDC/ASCT remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…21 The median OS was 1 year (range 0.5-14 years). Out of 26 patients, 2 were alive at the end of the follow-up period and 24 patients had died, of whom 22 patients succumbed to DFD and 2 patients succumbed to DFC.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 In group B, 26 patients with more than three bones involved at diagnosis (aged 6-37 years; median: 17 years) were registered from 1992 to 1996 and treated according to the European Intergroup Cooperative Ewing Sarcoma Study 92 protocol (EICESS 92) for high-risk ET-MBM, as previously described. 21 In all, 1 out of 26 patients had LN metastases and 10 out of 26 patients had lung disease at initial diagnosis. Group B patients did not receive TB-MRI at staging, and thus did not receive TB-MRI-governed ICI.…”
Section: Patient Characteristicsmentioning
confidence: 99%